Five new species of the tribe Gyrophaenina Kraatz 1830 (Coleoptera: Staphylinidae: Aleocharinae) from the southern part of the United States - Enushchenko, Ilya V. (Zootaxa, 2018)
Four new species of Gyrophaena Mannerheim, 1830 and one of Phanerota Casey, 1906 from southern states of the USA are described and illustrated: G. affinifera Enushchenko, sp.n. (Alabama), G. fontanedai Enushchenko, sp.n. (Alabama, Florida), G. marjakata Enushchenko, sp.n. (Arizona), G. velada Enushchenko, sp.n. (Arizona), and Ph. paradissimilis Enushchenko, sp.n. (Florida). A new species group is erected, the nitidula-group, containing G. nitidula (Gyllenhal 1810), G. pseudonitidula Semenov 2015 and G. fontanedai Enushchenko, sp.n., and a key for the species of this group is given.